Eco-environmental quality assessment of transition region between Qinling Mountains and Huanghuai Plain using Remote Sensing Ecological Index - Nannan Wu; Shijie Wang; Xiangjin Wu; Wenxiao Dong; Fang Huang; Haopeng Wang (Geocarto International)
Taking the transitional region between Qinling Mountains and Huanghuai Plain as the research object, RSEI model, Sen-Mann-Kendall and geographical detector were used to explore the temporal and spatial change characteristics and influencing factors of eco-environment quality from 2000-2020. The results show that: (1) The eco-environmental quality of the 20 years shows an increasing trend and the overall situation is good, but the heterogeneity of the spatial law is significant. (2) The spatial change trend of eco-environmental quality showed that 46.5% of the areas improved and 19.2% degraded, with frequent transfers and poor stability. (3) Greenness, dryness, land use type and slope were the main influencing factors, and showed an interactive enhancement. The results provide reference and new research perspectives for the rapid evaluation of the eco-environmental quality in the medium-scale natural geographical transition zone, and provide policy recommendations for the eco-environment protection and restoration in the transition zone between mountains and plains.